The simplified courtyard and its public space in north China’s small cities: significance, threats, and opportunities - Liu, Qian; Pezzetti, Laura (AESOP, 2023)
This study defined as ‘Simplified Courtyard’ a type of urban house widely built in the 1970s 1990s in small cities in North China. Together with their public and semi-public spaces, Simplified Courtyards constituted the urban landscape characteristic of the early socialist era in small cities. In the rapid urban transformation of the past few decades, a large part of them was demolished and replaced with a tabula rasa approach. Taking the small city Zhengding as an example, this study investigated the Simplified Courtyard with respect to its public space, analysing its urban significance, threats, and opportunities for regeneration, to draw adequate attention to this unique but long neglected urban component and contribute to their sustainable subsistence in the future. Keywords: Simplified Courtyard, public space, urban regeneration
Book of proceedings: 35th AESOP Annual Congress Integrated planning in a world of turbulence, Łódź, 11-15th July, 2023